Advertisement Remove all ads

F(X) = 4x4 − 3x3 − 2x2 + X − 7, G(X) = X − 1 - Mathematics

Answer in Brief

f(x) = 4x4 − 3x3 − 2x2 + x − 7, g(x) = x − 1

Advertisement Remove all ads

Solution

Let us denote the given polynomials as

`f (x) = 4x^4 - 3x^3 - 2x^2 + x - 7`

`g(x) = x-1`

We have to find the remainder when f(x) is divided byg(x).

By the remainder theorem, when f(x) is divided by g(x) the remainder is

`f(1) = 4(1)^4 - 3(1)^3 - 2(1)^2 + 1-7`

        ` = 4 - 3- 2 + 1- 7`

         ` = -7`

Now we will show remainder by actual division

So the remainder by actual division is −7

  Is there an error in this question or solution?
Advertisement Remove all ads

APPEARS IN

RD Sharma Mathematics for Class 9
Chapter 6 Factorisation of Polynomials
Exercise 6.3 | Q 2 | Page 14
Advertisement Remove all ads
Advertisement Remove all ads
Share
Notifications

View all notifications


      Forgot password?
View in app×